A Moving Equilibrium of Demand and Supply - Moore, Henry Ludwell (Quarterly Journal of Economics, 1925)
Elasticity of demand and flexibility of prices. — Relative cost of production and relative efficiency of organization, 359. — Laws of relative cost and relative return as contrasted with laws of cost and laws of return, 360. — Typical equations to the law of supply, 364. — The statistical derivation of the law of supply, 367. — A moving equilibrium of demand and supply, 368.